Budaya Kerja Islami sebagai Strategi Penguatan Kinerja Karyawan KSPPS BMT UGT Nusantara Cabang Riam Durian - Aulia Sindy Perwirasari, Dwi Tri Nilasari (Konsorsium Dosen Institut Agama Islam Al-Yasini Pasuruan, 2026)
: Improving employee performance in Islamic cooperatives should not only focus on achieving financial targets, but also be in line with Islamic values. This study was motivated by the lack of empirical studies discussing the role of Islamic work culture as a strategy for strengthening employee performance, particularly at BMT UGT Nusantara's Riam Durian Branch. This study aims to examine the application of Islamic work culture and employee performance improvement at BMT UGT Nusantara Riam Durian Branch. The research method used a qualitative approach with data collection techniques through semi-structured interviews, field observations, and source triangulation. The sources in this study consisted of branch managers and operational employees. Findings from the study indicate that the implementation of Islamic work culture through the practice of Islamic activities such as spiritual movement, recitation, and completion of the Qur'an has succeeded in internalizing the values of STAF (Shiddiq, Tabligh, Amanah, and Fathonah) into each employee. The culture of discussion and the exemplary leadership of managers can improve employee performance. This performance improvement is reflected in better work quality, the achievement of work quantity targets, the formation of a solid team based on Islamic brotherhood, and the emergence of work initiatives and motivation based on spiritual awareness. This study concludes that Islamic work culture not only functions as an organizational identity but also plays an effective and sustainable role in improving employee performance at BMT UGT Nusantara